2014
DOI: 10.1007/s10714-013-1662-2
|View full text |Cite
|
Sign up to set email alerts
|

Schwarzschild mass uncertainty

Abstract: Applying Dirac's procedure to r-dependent constrained systems, we derive a reduced total Hamiltonian, resembling an upside down harmonic oscillator, which generates the Schwarzschild solution in the mini super-spacetime. Associated with the now r-dependent Schrodinger equation is a tower of localized Guth-Pi-Barton wave packets, orthonormal and non-singular, admitting equally spaced average-'energy' levels. Our approach is characterized by a universal quantum mechanical uncertainty structure which enters the g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…An analogy between the Schwarzschild-Reissner-Nordström black holes and hydrogen atoms were drawn in [52,53], where their energy spectrum was obtained based on some constructed Schrödinger type of equation. A study related to a mass operator and the existence of non-zero mass uncertainty can be found in [54,55]. The quantization of an inhomogeneous cosmological model has been performed in [56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…An analogy between the Schwarzschild-Reissner-Nordström black holes and hydrogen atoms were drawn in [52,53], where their energy spectrum was obtained based on some constructed Schrödinger type of equation. A study related to a mass operator and the existence of non-zero mass uncertainty can be found in [54,55]. The quantization of an inhomogeneous cosmological model has been performed in [56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%
“…An analogy between the Schwarzschild-Reissner-Nordström black holes and hydrogen atoms were drawn in [51,52], where their energy spectrum was obtained based on some constructed Schrödinger type equation. A study related to a mass operator and existence of non-zero mass uncertainty can be found here [53,54]. The quantization of an inhomogeneous cosmological model has been performed in [55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [50] described a quantum Schwarzschild black hole by a non-singular wave packet composed of plane wave eigenstates of the momentum Dirac-conjugate to the mass operator. Furthermore, in [51], they provided an interpretation to an emergent spacetime as the quantum mechanical Schwarzschild vacuum, which appears to be massless, but exhibits non-zero mass uncertainty. These are only a few examples of the full list of quantum minisuperspace models.…”
Section: Introductionmentioning
confidence: 99%